The public health role of Histoplasma capsulatum (Revista Sistemas de Producción Agroecológicos, 2015)
Histoplasmosis or reticuloendothelial citomicosis or cave or Darling disease, is caused by the fungus Histoplasma capsulatum, which by lack of control policies, has presented high rates of morbidity and mortality in humans and animals, affecting labor productivity and animal husbandry. It has also proved a global crisis, by ignorance of the clinical method, underestimating the importance of the doctor-patient relationship, and no interrogation. The work activities that predispose to disease presentation are: speleologists, guano collectors, mining, rural workers (biologists and veterinarians), which are in direct contact with poultry or poultry manure handling and tourists who have contact mainly with caves, currently are included people working in earthmoving, cleaning or demolition of old buildings and logging. The H. capsulatum has three major varieties which have a wide geographical distribution and with high pathogenic potential which affects humans and animals, found to H. capsulatum var. capsulatum is endemic in America and some countries in Africa, Asia and Europe, while the H. capsulatum var. farciminosum (HCF), produce equine disease known as Epizootic lymphangitis, which is reported in Africa, Asia and Europe, also affecting mules, asinine, camels and cattle, that they are contaminated by contact with fomites and soil, harboring spores of this fungus, his transmission can occur, through abrasions on the integument; for example by tick infestations as mechanical vectors. Moreover in humans, most affected patients have an asymptomatic course due to their immune response. H. capsulatum fail the lung epithelial cells expecting the host be immunocompromised for other diseases such as HIV, cancer, chronic alcoholism, and immunosuppressive drugs, for generating a reactivation of endogenous infection. There are no studies that report infections with the fungus, through water or food, nor transmission from person-person or animal-person. For now, eradicate the fungus from affected ecosystems is really difficult, all that remains is prevention and education to the population, for avoid the contamination with histoplasmosis, is recommended in people with immunosuppression, not assist to places that have been labeled as reservoirs of fungus as caves.
Keywords: histoplasmosis; chiropterans; pigeon; occupational disease